2021
DOI: 10.1136/bmjgh-2020-003644
|View full text |Cite
|
Sign up to set email alerts
|

The impact of care environment on the mental health of orphaned, separated and street-connected children and adolescents in western Kenya: a prospective cohort analysis

Abstract: IntroductionThe effect of care environment on orphaned and separated children and adolescents’ (OSCA) mental health is not well characterised in sub-Saharan Africa. We compared the risk of incident post-traumatic stress disorder (PTSD), depression, anxiety and suicidality among OSCA living in Charitable Children’s Institutions (CCIs), family-based care (FBC) and street-connected children and youth (SCY).MethodsThis prospective cohort followed up OSCA from 300 randomly selected households (FBC), 19 CCIs and 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
(44 reference statements)
3
7
0
Order By: Relevance
“… 5 Our data suggest that, when compared directly with orphaned and separated youths in family-based settings, the differences between care environments were minimal, and living in an institutional setting may be associated with some protective benefits. 23 , 24 , 31 , 32 , 42 Our data are consistent with the findings of another study, which reported that the quality of care within care environments was more important to a child’s well-being than differences between care environment types. 25 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 5 Our data suggest that, when compared directly with orphaned and separated youths in family-based settings, the differences between care environments were minimal, and living in an institutional setting may be associated with some protective benefits. 23 , 24 , 31 , 32 , 42 Our data are consistent with the findings of another study, which reported that the quality of care within care environments was more important to a child’s well-being than differences between care environment types. 25 …”
Section: Discussionsupporting
confidence: 90%
“…Participants completed a standardized clinical evaluation annually (or semiannually for street-connected youths), and children 10 years and older completed an additional psychosocial evaluation annually. 31 The clinical encounter was an enhanced well-child care visit that included a complete survey of physical history and a review of symptoms. Household-level data were obtained through annual site assessments administered by the project manager (for charitable children’s institutions) or community health workers (for participating households).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Korzh (2015) points out that institutionalized children lack many educational and economic opportunities for full integration into society. Inconsistency with the present study, various studies conducted in low- and medium-income countries consider institutions to be a better place for upbringing (Omari et al, 2021). This author speculates that there are two main reasons for this: the religious nature of the structures and the presence of a vocational caregiver profile.…”
Section: Discussionsupporting
confidence: 85%
“…Children are the guarantors of this survival (Andrews et al, 2020). The interdependent nature of childhood and community reinforces the responsibility of the second for caring for all its members; therefore, any agent in the environment will be relevant for decision-making on care/rearing practice (Andrews et al, 2020), especially in circumstances of extreme vulnerability, where institutionalization is resorted to for the care of children (Omari et al, 2021). Transcultural nursing (TN) has developed different approaches to the above elements (Leininger, 2002; Purnell, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation